Amantadine, new look at the well-known medicine - Andrzej Stańczak; Wieslawa Lewgowd (Polish Pharmaceutical Society, 2022)
Amantadine is the medicinal product used in influenza A virus infections. It exhibits a dual mechanism of action: it inhibits the replication of the virus and blocks the process of its pene-tration into the host cells. Currently, this medicine is rarely used in the treatment of influenza due to the high antigenic variability of the virus, the availability of more effective antiviral products and preventive vaccinations. Taking into account its virostatic mechanism of action, amantadine was tested in vitro for the ability to inhibit replication of Human immunodeficiency virus type 1, Hepatitis C virus. How-ever, the results obtained were not satisfactory. Only its acetamide derivative (thromantadine) showed the expected properties, and it is a medicine that is also effective against Herpes sim-plex viruses Type 1, 2 and Varicella zoster virus. The SARS CoV 2 coronavirus pandemic has contributed to a renewed interest in amantadine. Taking into account that this medicinal product is an inhibitor of the E-protein ion channel that is a virulence determinant of SARS CoV 1 and the high degree of homology between SARS CoV 1 and SARS CoV 2, attempts have been made to use amantadine for COVID 19 therapy. The observations, as well as the results of in vitro experiments, form the basis of the clinical trials currently being performed. The efficacy of amantadine in the symptomatic treatment of Parkinson's disease was disco-vered incidentally, and to this day the medicine has been widely used in the treatment of pa-tients suffering from this neurodegenerative disease, as well as in the alleviation of parkinson-ism and drug-induced extrapyramidal symptoms. The pharmacological effects of amantadine on neurotransmitters in the central nervous system are unique, although not fully elucidated. It mainly combines dopaminergic and glutaminergic properties, although cholinergic, sero-tonergic and noradrenergic systems are also involved. It is the agonistic effect of amantadine on dopaminergic receptors and the modulation of glutamatergic system function that gives the possibility of its use in the treatment of psychiatric and neurological diseases and provides neuroprotection. Taking advantage of amantadine's effect on neurotransmission in the central nervous sys-tem, the drug has been used (with varying success) for unapproved indications in alleviating the symptoms of many incurable diseases. Nevertheless, confirmation of its efficacy requires further clinical trials.